2012
DOI: 10.1016/j.jdeveco.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental regulation and trade openness in the presence of private mitigation

Abstract: Acknowledging the differential ability of individuals to privately mitigate the consequences of domestic pollution for their health is essential for an understanding of their demands for regulation of the environment and of trade in dirty goods, and for analysis of the implications of these demands for equilibrium policy choices. In a small open economy with exogenous policy, we first explain how private mitigation at a cost results in an unequal distribution of the health consequences of pollution in a manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recent research has studied the consequences of inequality for mitigating pollution exposure. Hotte and Winer (2012) Each of these theoretical studies is relevant for our work. In our study, we adopt a partial equilibrium approach.…”
Section: Pollution Exposure Inequality Resulted From Self-protection mentioning
confidence: 99%
“…Recent research has studied the consequences of inequality for mitigating pollution exposure. Hotte and Winer (2012) Each of these theoretical studies is relevant for our work. In our study, we adopt a partial equilibrium approach.…”
Section: Pollution Exposure Inequality Resulted From Self-protection mentioning
confidence: 99%
“…This analysis shows that a reduction in the median voter's income leads to a higher equilibrium tax rate. While Hotte and Winer (2012) introduced private mitigation, this study explores spatial aspects to address the issue. The analysis focuses on a case in which averting behavior does not effectively improve the problem and, hence, a possible solution is to reside away from the point-specific hazardous site.…”
Section: Resultsmentioning
confidence: 99%
“…McConnell (1997) also indicated that the collective demand for environmental improvements is less responsive to income because the propensity for private mitigation, including residential choice, increases with income. Hotte and Winer (2012) built a theoretical model by introducing private mitigation. According to their model, the rich may spend more money on their own protection from pollution and do not necessarily require governmental regulation; hence, the demand for a more stringent environmental policy decreases as income levels rise.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is straightforward to extend the model to the case where workers are not equally vulnerable to the externality (see Footnote 16). See also Hotte and Winer () for a model where individuals are not equally vulnerable to pollution and can privately mitigate its impact.…”
mentioning
confidence: 99%